2009
DOI: 10.1158/0008-5472.can-08-3717
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Up-regulates p21 Expression by Site-Specific Inhibition of Histone Deacetylase 2/Histone Deacetylase 4 Association to the Locus

Abstract: Abstractp21 loss has been implicated in conferring oncogenic activity to known tumor suppressor gene KLF4 and cancer drug tamoxifen. Regulators of p21, therefore, play critical roles in tumorigenesis. Here, we report that X-linked tumor suppressor FOXP3 is essential for p21 expression in normal epithelia and that lack of FOXP3 is associated with p21 down-regulation in breast cancer samples. A specific FOXP3 binding site in the intron 1 is essential for p21 induction by FOXP3. FOXP3 specifically inhibited bindi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 35 publications
(62 reference statements)
6
122
1
Order By: Relevance
“…Previous results have shown that class-IIa HDACs can control CDKN1A expression (Liu et al, 2009;Mottet et al, 2009;Saramaki et al, 2009;Wilson et al, 2008); however, the mechanisms involved are debated. MEF2-binding sites are present in the genomic regions surrounding CDKN1A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that class-IIa HDACs can control CDKN1A expression (Liu et al, 2009;Mottet et al, 2009;Saramaki et al, 2009;Wilson et al, 2008); however, the mechanisms involved are debated. MEF2-binding sites are present in the genomic regions surrounding CDKN1A.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting data on the relationship between p21 expression and outcome in breast cancer (138). The role of p21 in tamoxifen response has not been studied extensively, although the ERBB2 repressor forkhead box P3 is essential for p21 expression (143) and there is some evidence for p21 de-regulation in cancers with ERBB2 over-expression or AKT activation (139). The latter results in the mis-localization of p21 to the cytoplasm, a phenomenon associated with poor response to tamoxifen (144).…”
Section: Co-activators and Co-repressorsmentioning
confidence: 99%
“…For example, FOXP3 directly represses the ERBB2 and SKP2 oncogenes while maintaining the expression of the p21 tumour suppressor in the breast epithelium (Zuo et al, 2007a, b;Liu et al, 2009). In prostate cells, FOXP3 has also been shown to directly repress c-myc transcription , an oncogene frequently overexpressed in many human cancers (Wolfer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%